An Overview of Islamic Law in the Mechanism of Individual Distribution if the Wife of the Heir is more than One - Ani Maryani; Umar Ma'ruf; Winanto Winanto (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
This study aims to determine and analyze the mechanism of inheritance distribution if the wife of the heir is more than one in terms of Islamic law. The research approach method used in the preparation of this thesis is a normative juridical research method. This research specification uses descriptive analysis. The type of data used is secondary data from legal materials in the form of the Qur'an and Hadith, the Civil Code, the Marriage Law, and the Compilation of Islamic Law. Collecting data by studying documents or library materials that are collected and processed systematically. The results of this study indicate that: first, the acquisition of inheritance rights for wives or wives is contained in the Qur'an letter An-Nisa' verse 12 and in the Compilation of Islamic Law Article 180. After removing part of the joint property, the rest is distributed to the heirs. If the heir leaves children, the wife's share is 1/8 and if the heir does not leave children, the wife's share is of the inheritance. Second: The concept of marriage in Indonesia based on Act No. 16 of 2019 concerning amendments to Act No. 1 of 1974 concerning marriage contains elements of monogamy, but the court can grant permission on fair conditions, the wife's consent, guarantees the necessities of life for the wife and children, and permit has permanent legal force. KHI explains that joint assets in each marriage are separate and independent and are calculated at the time of the second, third or fourth marriage contract.